International sport management - MacIntosh, Eric W.; Li, Ming; Bravo, Gonzalo A. (Human Kinetics, 2020)
International Sport Management, Second Edition, takes a comprehensive look at the organization, governance, business activities, and cross-cultural context of modern sport on an international level. As the sport industry continues its global expansion, this second edition serves as an invaluable guide for students as they build careers that require an international understanding of the relationships, influences, and responsibilities in sport management. With a diverse editorial team and assembly of contributors from all corners of the globe, this text presents a truly international perspective that showcases how sport operates in various geopolitical environments and cultures. The second edition has been updated to address current issues in the industry: • An engaging new opening chapter on growth in international sport • A standardized organization of the part II chapters for easier comparison across regions, including new and expanded chapters on sport in Western Europe, Eastern Europe, Latin America and the Caribbean, and the Arab world • A new chapter dedicated to social media in international sport • New content on corruption and doping in sport, including examples from the Olympics International Sport Management, Second Edition, prepares students to apply global management strategies in the business segments of sport marketing, sport media and information technology, sport event management, and sport tourism. Case studies and sidebars apply the concepts to real-world situations and demonstrate the challenges and opportunities that future sport managers will face on a regular basis. Instructor ancillaries are available at www.HumanKinetics.com/InternationalSportManagement